2015
DOI: 10.3168/jds.2015-9726
|View full text |Cite
|
Sign up to set email alerts
|

The rapid increase of circulating adiponectin in neonatal calves depends on colostrum intake

Abstract: Adiponectin, an adipokine, regulates metabolism and insulin sensitivity. Considering that the transplacental transfer of maternal proteins of high molecular weight is hindered in ruminants, this study tested the hypothesis that the blood concentration of adiponectin in neonatal calves largely reflects their endogenous synthesis whereby the intake of colostrum might modify the circulating concentrations. We thus characterized the adiponectin concentrations in neonatal and young calves that were fed either colos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
1
19
1
Order By: Relevance
“…However, postprandial time changes in plasma leptin and adiponectin after first feed intake behaved differently-both hormones increased after first colostrum feeding-showing the same postprandial time pattern as that observed for plasma concentrations of total protein and immunoglobulins. Both hormones are highly concentrated in first colostrum (Kesser et al, 2015(Kesser et al, , 2017, and the absorption of adiponectin from first colostrum was recently shown in neonatal calves (Kesser et al, 2015). Leptin absorption from colostrum was less clear in previous studies, but an elevated plasma concentration of leptin was also associated with colostrum feeding (Blum et al, 2005;Schäff et al, 2014;Kesser et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, postprandial time changes in plasma leptin and adiponectin after first feed intake behaved differently-both hormones increased after first colostrum feeding-showing the same postprandial time pattern as that observed for plasma concentrations of total protein and immunoglobulins. Both hormones are highly concentrated in first colostrum (Kesser et al, 2015(Kesser et al, , 2017, and the absorption of adiponectin from first colostrum was recently shown in neonatal calves (Kesser et al, 2015). Leptin absorption from colostrum was less clear in previous studies, but an elevated plasma concentration of leptin was also associated with colostrum feeding (Blum et al, 2005;Schäff et al, 2014;Kesser et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Absorption of colostral leptin occurs in rats and humans (Szymeczko et al, 2009;Woliński et al, 2014;Palou et al, 2018). Previous studies indicated lower leptin and adiponectin concentrations in milk or milk-based formulas than in colostrum (Kesser et al, 2015(Kesser et al, , 2017. The lack of time changes in leptin and adiponectin in blood plasma of formula-fed calves on d 1 of life makes it very clear that the increase in leptin and adiponectin plasma concentrations after first colostrum feeding resulted from intestinal absorption of both hormones and that both hormones behaved differently than colostral IGF-I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8019, Quidel MicroVue, San Diego, CA). Serum adiponectin concentration was measured by ELISA as described by Kesser et al (2015). Serum leptin concentration was measured by ELISA as described by Sauerwein et al (2004), and haptoglobin (Hp) concentration was measured in serum by enzyme immunoassay as described by Hiss et al (2009).…”
Section: Variables Measured In Plasma and Serummentioning
confidence: 99%
“…In addition, postprandial insulin concentration in the plasma after the first colostrum feeding was significantly higher in calves that were fed colostrum immediately after birth than in calves that were fed colostrum 24 hr after birth. In neonatal calves, the concentration of adiponectin, which has insulin‐sensitizing effects, rapidly increased 24 hr after colostrum intake, although this did not change after feeding with formula (Kesser et al., ). These reports strongly suggest that colostrum has a pivotal role in the growth of the neonate.…”
Section: Introductionmentioning
confidence: 99%